Effect of post-mastectomy radiation therapy on survival in breast cancer with lymph nodes micrometastases: a meta-analysis and systematic review - Zheng, Jianqing; Huang, Bifen; Chen, Ying; Chen, Zhangzhu (Frontiers in Oncology, 2025)
BackgroundAxillary management of patients with early-stage breast cancer (ESBC) has evolved, especially with the implementation of precision radiotherapy techniques that have resulted in a significant reduction in treatment-related toxicities, but it is unclear whether post-mastectomy radiotherapy (PMRT) improves survival outcomes in breast cancer with lymph nodes micrometastases (BCLNMM, that is T0, T1 ~2NmiM0). Our study is to systematically evaluate the effect of PMRT on survival in breast cancer with lymph nodes micrometastases.MethodsA literature search was performed for randomized controlled trials (RCTs) or retrospective studies related to PMRT versus non-post-mastectomy radiotherapy (non-PMRT) in the adjuvant treatment of ESBC in PubMed, Cochrane Library, Embase, CNKI and other databases. R package meta software was used to perform meta-analyses with hazard ratio (HR). Newcastle Ottawa scale was selected for quality assessment. The review was prospectively registered on PROSPERO (CRD42024562444).Results10 relevant studies were screened, all of which were retrospective studies. The difference in overall survival (OS) was not statistically significant (HR = 0.92, 95%CI: 0.81 ~ 1.04; Z = 1.35, P = 0.177). The difference in breast cancer-specific survival (BCSS) between the PMRT group and the non-PMRT group was not statistically significant HR = 1.18, 95%CI: 0.94 ~ 1.48; Z = 1.41, P =0.160). The difference in disease-free survival (DFS) was statistically significant (HR = 0.47, 95%CI: 0.23 ~ 1.00; Z = 1.96, P =0.049). The difference in local recurrence free survival (LRRFS) was also not statistically significant (HR = 0.50, 95%CI: 0.11 ~ 2.26, P = 0.190). The difference in distant-metastasis free survival (DMFS) was not statistically significant (HR = 0.54, 95%CI: 0.22 ~ 1.35, P = 0.356).ConclusionsDespite the tendency of PMRT in BCLNMM to improve DFS, OS, BCSS, LRRFS, and DMFS showed no benefit, therefore, PMRT should be used with caution in BCLNMM.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024562444.